If f ( &#x03B8;<!-- θ --> ) = s i n ( &#x03B8;<!-- θ --> ) =

Monserrat Sawyer 2022-05-29 Answered
If f ( θ ) = s i n ( θ ) = 0.1, then find f ( θ + π ) = s i n ( θ + π )
You can still ask an expert for help

Want to know more about Trigonometry?

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

vrhnjemuvs
Answered 2022-05-30 Author has 4 answers
You can do it by using the summation formula for sines
sin ( x + y ) = sin ( x ) cos ( y ) + sin ( y ) cos ( x )
just set y = π and you get
sin ( x + π ) = sin ( x ) cos ( π ) + sin ( π ) cos ( x ) = sin ( x ) ( 1 ) + 0 cos ( x ) = sin ( x )
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions